Information support for the training process of young swimmers by means of developing mobile applications - Volodymyr Ashanin; Ludmila Filenko; Andrii Kazmirchuk; Igor Filenko (Kharkiv State Academy of Physical Culture, 2020)
Purpose: substantiation of the need to develop a mobile application to control training loads in the preparation of young swimmers. Methods: theoretical analysis and synthesis of references; methods of information modeling & programming, questionnaire, methods of mathematical statistics. Results: «SwimmDiary» mobile application was developed on the Android Studio and Java platforms; the development is aimed at individualizing control and planning of physical activity in young swimmers. The development allows you to create and adjust a personal profile of an athlete, register individual indicators, establish a daily training program in the calendar, view existing standards and compare your own results with them, statistics of physical activities performed for a specific training period. The program includes such indicators as: the name of the physical exercises, the time of their completion, the mileage of the preparatory exercises to cover the main distance. The mobile application contains the following swimming styles: butterfly stroke, brass, crawl on the back, freestyle and integrated swimming style. A questionnaire was conducted, the main purpose of which was to identify the respondents' attitude to the mobile application. It was found that young athletes liked the development the most (11.2 ± 0.07), and their parents gave the lowest marks (8.3 ± 0.08) on a 12-point scale. Conclusions: it was found that the use of modern information technologies in the educational process of young swimmers is possible using mobile applications, survey of respondents found a high level of attitude towards the development of young swimmers, coaches and swimming scientists. The survey revealed a high level of evaluation of respondents of the mobile application SwimmDiary (48%) and indicated the strongest components of the program (design solution and presentation of the mobile application) and weak (data visualization).